Avaliação reprodutiva de touros bubalinos alimentados com subprodutos da agroindústria na Amazônia Oriental - SANTOS, Alessandra Ximenes (Universidade Federal do Pará, 2014)
The byproducts coconut meal (FC) and palm kernel cake (TAD) available in agribusiness in Eastern Amazonia can be used as alternative foods in the substitution of conventional concentrates. However, little information about their chemical composition and their relationship with productive and reproductive performance of the animals is available. Thus, the aim of this study was to evaluate the effect of the feeds prepared with coconut meal and palm kernel cake over the semen quality of buffaloes. Also, the individual daily feed intake in the experimental diets and your relationship with the testosterone levels, scrotal circumference and semen quality were analyzed. The experiment was developed in the Animal Research Unit "Senador Álvaro Adolpho", in Embrapa Eastern Amazon, Belém-PA. Fifteen buffaloes (Bubalus bubalis) bulls with age of 3.2 ± 1.8 years and weights of 578.6 ± 101.9 kg were used as semen donors. The animals were separated in three groups: the Control group, the FC-Base group (coconut meal-based) and the TADBase group (palm kernel cake-based). The supplementary feeding was available individually every day, according 1.0% of body weight (BW). Semen collections (n=173) were realized weekly, and they started 112 days after initiation of supplementary feeding, after two spermatogenic cycles. Seminal physical characteristics (aspect, color, volume, concentration, pH, sperm motility and vigor) and morphology (defects and integrity of sperm plasma membrane) were analyzed. The EPA method (1974, 1994, 2009) was used to determine the macronutrients, micronutrients and toxic metals in diets. Data were submitted to ANOVA and the means compared by Test t (P<0.05). The average feed intake was 4.778 ± 1.233 kg in the Control, 3.112 ± 0.693 kg in the FC-Base, and 4.558 ± 1,077 kg in the TADBase. The means of weight were 591.4 ± 103.3 kg, 566.4 ± 94.1 kg and 578.3 ± 107.5 kg and the scrotal circumference of 34.6 ± 2.0 cm, 33.0 ± 1.9 cm e 32.7 ± 1.9 cm for Control, FC-Base and TAD-Base, respectively. The spermatic concentration (x106 sptz/mL) was 1326.3 ± 893.8, 1698.1 ± 1023.0 e 1003.2 ± 569.0 for Control, FC-Base and TAD-Base, respectively. In the same order, the integrity of sperm plasma membrane (%) observed was 68.0 ± 19.5, 72.0 ± 22.6 and 82.1 ± 12.2. The progressive sperm motility (0-100%) presented significant difference (P<0.05) in the TAD-Base group (71.7 ± 15.1%), compared to Control (59.3 ± 20.5%) and FC-Base (56.7 ± 24.8%). Correlations were observed between the variables of response. The feed intake and your components, such as crude protein, lipids, macronutrients, micronutrients and toxic metals were higher in the TAD-Base group, exception to K and Ti, higher in the Control and the FC-Base group, respectively. No significant differences (P>0.05) were observed in semen aspect, volume, mass activity, spermatic vigor, pH and sperm pathologies. However, higher sperm concentrations were observed in FC-Base and increased motility and integrity of sperm plasma membrane in the TAD-Base. Thus, it can be concluded that diets based on byproducts of the agribusiness, such as coconut meal and palm kernel cake, can be used for buffalo bulls, however, the better semen quality was observed in diets based on palm kernel cake.